(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Upper and lower extremity musculoskeletal disorders (MSDs) are prevalent among the general population and impose a substantial cost on the healthcare system. Clinical practice guidelines encourage the use of manual therapy for managing these injuries. However, there is insufficient data to fully support its usefulness. The objective of our study was to examine the efficacy of manual treatment in adults or kids with musculoskeletal disorders (MSDs) affecting the upper or lower extremities. We conducted a comprehensive search of the CINAHL, EMBASE, MEDLINE, PsycINFO, and the Cochrane Database of Controlled Trials databases. The reviewers worked together to evaluate the studies for their relevance and conducted a thorough assessment of the relevant research following the criteria set by the Scottish Intercollegiate Recommendations Network. Studies that had a low risk of bias were combined using the criteria of best-evidence synthesis. When possible, we calculated the average differences between groups, the relative risks, and the 95% confidence intervals. In people with nonspecific shoulder discomfort of varying duration, the inclusion of cervicothoracic spinal adjustment and mobilization to normal therapy may enhance self-perceived healing in comparison to standard treatment alone. Adding neck mobilization to a multidisciplinary shoulder course of therapy does not give any additional benefit for persons with subacromial friction condition of varying duration. In conclusion, for adults who have grade I-II ankle ligament sprains of varying lengths, using lower extremity mobilization together with home exercise and advice yields more significant short-term enhancements in activity and function compared to only relying on home exercise and advice. No research investigations were incorporated that assessed the efficacy of manual therapy for kids or for the treatment of various injuries in adults affecting the limbs. There is insufficient data about the efficacy of manual treatment for musculoskeletal disorders (MSDs) affecting the upper and lower limbs. The existing data substantiates the efficacy of manual therapy in treating non-specific shoulder discomfort and ankle sprains. However, it does not support the application of manual treatment for subacromial friction condition in adults. Further investigation is required to ascertain the efficacy of manual treatment and provide guidance for clinical use.